Detection of cancers and advanced adenomas in asymptomatic participants in colorectal cancer screening: a cross-sectional study. Issue 7 (1st July 2021) - Schult, Anna Lisa; Botteri, Edoardo; Hoff, Geir; Randel, Kristin R; Dalén, Eirin; Eskeland, Sigrun Losada; Holme, Øyvind; de Lange, Thomas
Abstract : Objectives: To assess detection rates for colorectal cancer (CRC) and advanced adenomas in asymptomatic CRC screening participants and bowel symptoms in association with CRC and advanced adenoma. Design: Cross-sectional study. Setting: Two screening centres. Participants: 42 554 men and women, aged 50–74 years, participating in a randomised CRC screening trial. 36 059 participants underwent a sigmoidoscopy (and follow-up colonoscopy if positive sigmoidoscopy) and 6495 underwent a colonoscopy after a positive faecal immunochemical test (FIT). Primary and secondary outcome measures: Proportion of asymptomatic participants diagnosed with CRC or advanced adenomas. Prevalence of bowel symptoms (rectal bleeding, change in bowel habits, diarrhoea, constipation, bloating, alternating bowel habits, general symptoms, other bowel symptoms) recorded by the endoscopist and their association with CRC and advanced adenomas. Results: Among sigmoidoscopy participants, 7336 (20.3%) reported at least one symptom. 120 (60%) out of 200 individuals with screen-detected CRC and 1301 (76.5%) out of 1700 with advanced adenoma were asymptomatic. Rectal bleeding was associated with detection of CRC and advanced adenoma (OR 4.3, 95% CI 3.1 to 6.1 and 1.8, 95% CI 1.5 to 2.1, respectively), while change in bowel habits only with CRC detection (OR 3.8, 95% CI 2.4 to 6.1). Among the FIT positives, 2173 (33.5%) reported at least one symptom. Out of 299 individuals with screen-detected CRC and 1639 with advanced adenoma, 167 (55.9%) and 1 175 (71.7%) were asymptomatic, respectively. Detection of CRC was associated with rectal bleeding (OR 1.8, 95% CI 1.4 to 2.3), change in bowel habits (OR 2.2, 95% CI 1.4 to 3.5) and abdominal pain (OR 1.8, 95% CI 1.2 to 2.7). Conclusions: Some bowel symptoms increased the likelihood of being diagnosed with CRC or advanced adenoma. However, the majority of individuals with these findings were asymptomatic. Asymptomatic individuals should be encouraged to participate in CRC screening. Trial registration number: Clinicaltrials.gov Identifier: NCT01538550 .